Impacto de la contaminación de las aguas del río Itaya por las actividades portuarias en el puerto MASUSA - Cerdeña del Aguila, Carmen Patricia (2017)
ABSTRAC The impact of the pollution of the waters of the rio Itaya has been investigated by port activities that are generated in the puerto Masusa - Iquitos. A holistic approach, mixing the pre-experimental design (pollution of the waters of the rio Itaya), with transverse description (port activities) and comparative research (environmental impact) was used for the development of research. For this purpose, determined the contamination of the waters of the Itaya River on the shores of puerto Masusa, comparing the results of the physicochemical and microbiological analysis of the standard (the Amazon River behind port Masusa samples) versus the results of sampling (100 metres above the harbour - Harbour - 100 metres down the port). The sampling was carried out for two months (September and November 2011). It has been concluded that there is no significant difference in indicators: pH, oils and fats, BOD5, cod; and contamination by the presence of Esherichia. Coli. Port activities carried out in the port Masusa, were determined through surveys to nearby residents to the port, passengers and crew members of the motorboats, taking a stratified random sample. I will collect information in the Office of the authority port national - Iquitos (ANP) and the Directorate of water transport (DGTA) of the GÖREL. Results demonstrate that the activities of the port are very necessary and important for the economic development of the Loreto region, however they do not have adequate disposal of solid waste, have a low level of knowledge of environmental education and do not have a control by the authorities. The inhabitants do not have adequate bathrooms and mostly evacuate their wastewater into the river. Crews used water from the River to perform all cleaning activities and then throw them into the river. He impact environmental is determined through the matrix of Leopold and is determined that there is an impact environmental very seriously.